1997
DOI: 10.1111/j.1559-1816.1997.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Machines Gender Neutral? Gender‐Stereotypic Responses to Computers With Voices

Abstract: This study tested whether computers embedded with the most minimal gender cues will evoke gender‐based stereotypic responses. Using an experimental paradigm (N = 40) that involved computers with voice output, the study tested 3 gender‐based stereotypes under conditions in which all suggestions of gender were removed, with the sole exception of vocal cues. In all 3 cases, gender‐stereotypic responses were obtained. Because the experimental manipulation involved no deception regarding the source of the voices. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
268
1
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(322 citation statements)
references
References 15 publications
(8 reference statements)
11
268
1
10
Order By: Relevance
“…If people apply human gender stereotypes to machines, as some research suggests [31], the machine's perceived gender could influence users' trust as well. Therefore our field experiment had eight conditions in a 2 (user's expression modality: talk, type) × 2 (machine's response modality: talk, type) × 2 (machine's gender: male, female) between-participants fully randomized experimental design.…”
Section: Page 474mentioning
confidence: 99%
“…If people apply human gender stereotypes to machines, as some research suggests [31], the machine's perceived gender could influence users' trust as well. Therefore our field experiment had eight conditions in a 2 (user's expression modality: talk, type) × 2 (machine's response modality: talk, type) × 2 (machine's gender: male, female) between-participants fully randomized experimental design.…”
Section: Page 474mentioning
confidence: 99%
“…These researchers described themselves as functioning within the Computers as Social Actors (CASA) paradigm and argued that people may be unconsciously perceiving computers and other media as being intentional social agents (Nass, Moon, & Carney, 1999). Some studies showed that people often attributed human characteristics to computers: People were polite to machines (Nass et al, 1999), perceived machines as competent teammates (Nass, Fogg, & Moon, 1996), ascribed gender and personalities to machines (Nass, Moon, & Green, 1997), and got angry and punished them (Ferdig & Mishra, 2004). Responding socially to a computer was also quite common and typical for people of all ages and levels of expertise (Mishra, 2006).…”
Section: Source Of Feedbackmentioning
confidence: 99%
“…Since gender can influence trust in computer recommendation systems (Nass et al, 1997), we ensured that the advisors are female for all media representations (e.g., the same female audio tracks, female names). The sizes of the representations of the actor were made consistent in each media, by making sure that the video and avatar clips were projected at the same size, and at the same eye level, as the robot.…”
Section: Media Representationsmentioning
confidence: 99%